Understanding the Effect Size of Peer-Mediated Academic Instruction: A Meta-Analysis. (March 2022) - Haas, April; Vannest, Kimberly J.; Fuller, Marcus C.; Ganz, Jennifer B.
A deficit in social skills often makes teaching academics a second thought when instructing students with autism. Peer-mediated instruction has been well studied for increasing academic skills across various disabilities and social skills for students with autism spectrum disorder (ASD). The purpose of this study was to determine the effect size of peer-mediated academic instruction (PMAI) to increase academic skills for students with ASD. Results indicate studies demonstrate a weak to moderate effect when using PMAI to teach students with ASD. These results validate PMAI can be effective when teaching academic skills to students with ASD; however, more studies are needed to better understand for whom and under what conditions PMAI is most effective.